Ptosis induced by topical steroid eye drops: Two cases reports. Issue 51 (December 2017) - Zhu, Yanan; Sun, Chaohui; Zhang, Xin; Shentu, Xingchao
Abstract: Rationale: Ptosis is a rare complication of periocular steroid use. Studies report that local injections of steroids produce ptosis. We describe the first 2 cases of ptosis because of long-term treatment with topical steroid eye drops. Patient concerns: Two cases admitted to our hospital because of ptosis of their right eye after long-term treatment with topical steroid eye drops. Both of them had uncontrolled Posner–Schlossman syndrome. Diagnosis: Two cases were diagnosed as steroid-related ptosis. Interventions: Regulatory anti-inflammation therapy was prescribed for case 1, and after inflammation control, phacoemulsification was done for her. Six months after steroid withdrawal, the levator resection of the right eye was performed. Case 2 refused our advice of steroid reduction and ptosis surgery. Outcomes: After surgery, case 1 retained a symmetrical appearance during a 1-year follow-up. In the surgery, we found thin levator muscles and slack levator palpebrae superioris aponeurosis (LPSA) in the affected eye. Postoperative transmission electron microscopy revealed typical signs of apoptosis in levator muscle cells. Lessons: We suggest topical application of steroids induces levator muscle apoptosis and LPSA weakness, and results in ptosis.